The Role of Globalization in Indonesian Evolution Influence on Media Digital Literacy Language AI - Lutfiani, Ninda; Fauziyah, Nida; Oganda, Fitra Putri; Setyaningrum, Retno; Winanti; Padeli; Natalia, Ester Ananda (International Transactions on Artificial Intelligence, 2025)
Globalization has brought significant changes in various aspects of life, including language use. As the official language and a symbol of national cultural identity, the Indonesian language is not immune to the effects of globalization, particularly in mass media, literature, and academic publications. This article analyzes the impact of globalization on the use of the Indonesian language, with a focus on two main dimensions: literature and digital media. In literature, globalization tends to introduce foreign elements that influence language style and narrative structure, while in digital media, the use of Indonesian is often mixed with foreign languages and slang influenced by global trends. Furthermore, in academic publications, globalization introduces new terms that often use international languages, such as English, which reduces the use of Indonesian in scholarly contexts. This study also highlights the challenges faced in maintaining the standardization of the Indonesian language amid the rapid flow of globalization, emphasizing the crucial role of language institutions and society in preserving the language's integrity. Through this analysis, it is hoped that strategies will be identified to preserve the richness and standardization of the Indonesian language, ensuring its relevance in an increasingly globalized world.